Higher Education Research Productivity: The Influences of Different Forms of Human Capital - Callaghan, Chris William (South African Journal of Higher Education, 2016)
This study tests theory that predicts the potential influence of different manifestations of experience on higher education research productivity in the context of a large South African research university. The differential contribution of different forms of experience to research productivity is tested using correlation analysis, partial correlation analysis and hierarchical linear regression analysis. The results suggest that research productivity is relatively robust to forms of work experience other than that of being a researcher, that membership of professional associations is positively related to research productivity, and that years of formal education are not. It is concluded that research productivity may represent specific human capital; a form of tacit learning that may primarily be accessible only through a process of ‘learning by doing’. Implications arising from these findings are considered.